Relationship Between Academic Administration and Effectiveness of schools in the Chonburi 2 School Cluster under the Chonburi Rayong Secondary Educational Service Area Office - Wongniam, Napaporn; Thepsaeng, Somchai; Prachongchit, Sanan (Journal for Developing the Social and Community, 2023)
The objectives of this research were to study: 1) academic administration of the school, 2) school effectiveness, and 3) relationship between academic administration and effectiveness of schools in the Chonburi 2 School Cluster under the Chonburi Rayong Secondary Educational Service Area Office. A sample of 217 was randomly selected from teachers at these schools. The tool was a questionnaire. The statistics used in the analysis were frequency, percentage, mean, standard deviation. and Pearson’s correlation coefficient. The results were as follows. Academic administration of these schools was rated on overall and on individual aspects at the high level. Those aspects were ranked from the top as that of assessment and evaluation, of educational supervision, of development and usage of educational technology media, curriculum development, and guidance. The overall effectiveness of these schools was also rated the high level. However, two aspects, that of ability to produce high-achieving students and of ability to adapt and develop to suit the environment, were rated at the very high level, while the other two of ability to solve school internal problems, and of ability to develop students to have a positive attitude, rated at the high level only. Academic administration had a very high positive correlation with the effectiveness of schools in the Chonburi 2 School Cluster under the Chonburi Rayong Secondary Educational Service Area Office (r=0.879). It was statistically significant at the 0.05 level.